Determinants of adherence to evidence-based therapy after acute myocardial infarction. (29th August 2020) - Hamood, Hatem; Hamood, Rola; Green, Manfred S; Almog, Ronit
Abstract: Background: The extent to which drug adherence may be affected by patient characteristics remains unclear. This study investigated potential determinants of adherence to evidence-based cardioprotective medications in patients with acute myocardial infarction. Design: Patient-based retrospective cohort study of 4655 elderly one-year survivors of acute myocardial infarction, members of a health organization in Israel, between 2005 and 2010. Methods: All patients filled at least one prescription for any key medication. Adherence was measured using the proportion-of-days-covered (PDC) metric and defined as PDC ≥ 80%. Results: Nonadherence to aspirin, β-blockers, angiotensin converting enzyme inhibitors/angiotensin receptor blockers or statins approximated 50%, and 80% for combined therapy of all medications. In multivariable analyses, compared with nonadherents to all medications, adherers to at least one medication were more likely to be of Jewish origin (adjusted odds ratio (AOR), 2.11; 95% confidence interval (CI), 1.60–2.78), inhabitants of the central or northern districts, and attending a cardiologist at least once during the first year of follow-up (AOR, 1.26; 95% CI, 1.05–1.51). Increasing number of outpatient visits was associated with improved adherence and followed a significant dose–response gradient. Factors significantly associated with reduced adherence were presence of comorbid conditions, particularly chronic ischemic heart disease (AOR 0.69; 95% CI, 0.57–0.83) and readmissions (AOR, 0.65; 95% CI, 0.55–0.78). Results were consistent when evaluating adherence to each medication separately. Conclusions: Outpatient adherence to recommended therapy in patients with acute myocardial infarction is suboptimal and is related to health services utilization. Further research is needed to investigate patient subjective behavioral-related drivers for medication therapy discontinuation after myocardial infarction in the absence of a clinical reason.